THE EFFECT OF THE APPLICATION OF DISCOVERY LEARNING LEARNING MODELS ON HISTORICAL LEARNING RESULTS OF STUDENTS AT SMAN 1 NATAR, LAMPUNG SELATAN - Suparman Arif; Rinaldo Adi Pratama; Ali Imron (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2020)
History learning must bring students more active in the teaching and learning process, educators must be able to determine the right model for conducting the learning process in class. However, nowadays history learning in schools, especially at the public high school level is still far from student centered as expected by the 2013 curriculum.  This study used a Quasi Experiment type of research with nonequivalent pretest-posttest control group design that contains the experimental class and the control class. The data analysis technique used in this study used an independent t-test. The results showed that the historical learning outcomes of students who used the Discovery Learning model were higher than the students who used the direct learning model. The analysis results obtained by Sig. (2-tailed) 0,000 significance level α = 0.05, because the value of 0,000 < 0.05, this means that there are differences in the average historical outcomes learning between students who use the Discovery Learning model with the Direct Learning model.